FPGA realisation of inverse kinematics for biped robot based on CORDIC. Issue 5 (1st February 2013) - Wong, C.C.; Liu, C.C.
Abstract : A FPGA realisation structure based on CORDIC is proposed to implement inverse kinematics for a biped robot. First, the angle equations of inverse kinematics for the biped robot are described. Based on these equations represented by the inverse tangent function, a FPGA structure based on two CORDIC operators of circular vectoring and hyperbolic vectoring is proposed and implemented on a FPGA chip. Finally, comparison of the proposed FPGA realisation and the software realisation to calculate these angle equations is presented to illustrate the effectiveness of the proposed structure.